Gaining molecular insights towards inhibition of foodborne fungi Aspergillus fumigatus by a food colourant violacein via computational approach - R. Sindhu; Smitha S. Bhat; Jiraporn Sangta; Chandan Dharmashekar; Bhargav Shreevatsa; Chandan Shivamallu; Devananda Devegowda; Shiva Prasad Kollur; Sheikh F. Ahmad; Sabry M. Attia; Sarana Rose Sommano; Shashanka K. Prasad (Scientific Reports)
Abstract Filamentous Fungal Human Pathogens (FFHPs) such as Aspergillus fumigatus, are growing resistant to currently available antifungal drugs. One possible target, the Nucleoside diphosphate kinase (Ndk) is significant for nucleotide biosynthesis and crucial for fungal metabolism. Violacein, a natural food colorant, was examined for its antifungal effects against Aspergillus fumigatus via computational approach against the Ndk protein. Known and predicted interactions of Ndk with proteins was performed using the STRING application. Molecular docking was performed using Schrodinger Maestro software (V.14.1) under enhanced precision docking, with OPLS4 forcefield. MDS was performed for 500ns under OPLS4 forcefield and the TIP3P solvent system. The geometry optimization for DFT was performed using the Becke 3-parameter exchange functional (B3LYP) method. The Molecular Docking Studies revealed significant interactions with good binding energy between Violacein and Ndk. Subsequent MD Simulations confirmed the stability of Violacein-Ndk complex, compared to the reference ligand-complex, indicating a stable interaction between the protein and violacein. The energy band gap of violacein was found to be 0.072567 eV suggesting its softness with lower kinetic stability and higher chemical reactivity. The results suggest Violacein could potentially disrupt nucleotide metabolism by targeting Ndk, thus demonstrating antifungal activity. However, further experimental validation is required to confirm these computational findings and explore the practical use of Violacein in antifungal treatments.